2002
DOI: 10.1007/bf02256538
|View full text |Cite
|
Sign up to set email alerts
|

Purine, kynurenine, neopterin and lipid peroxidation levels in inflammatory bowel disease

Abstract: The kynurenine metabolites of tryptophan may be involved in the regulation of neuronal activity and thus gut motility and secretion. We have now performed a pilot study to measure serum concentrations of purines and kynurenines in patients with mild inflammatory bowel disease, as well as in sex- and age-matched control subjects. For some analyses, the patients were subdivided into subgroups of those with Crohn's disease and those with ulcerative colitis. The analyses indicated an increased activity in one bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 39 publications
2
31
1
1
Order By: Relevance
“…Forrest et al [21] detected an increased level of serum KYNA in patients with inflammatory bowel disease. In contrast, a decreased plasma content of KYNA was found in patients with irritable bowel syndrome [22].…”
Section: Discussionmentioning
confidence: 98%
“…Forrest et al [21] detected an increased level of serum KYNA in patients with inflammatory bowel disease. In contrast, a decreased plasma content of KYNA was found in patients with irritable bowel syndrome [22].…”
Section: Discussionmentioning
confidence: 98%
“…Patients with mild inflammatory bowel disease (Crohn's disease and ulcerative colitis) exhibited an increased level of KYNA, which may be either a compensatory response to the enhanced activation of enteric neurons, or a primary abnormality which induces a compensatory increase in gut activity (Forrest et al, 2002).…”
Section: Bowel Diseasementioning
confidence: 99%
“…Activated lymphocytes T were proved to synthesize interferon-γ, which stimulates the release of NPT from monocytes/macrophages [5][6][7]. Previous studies confirmed the usefulness of NPT as a clinical marker of many autoimmune conditions [5,8,9], e.g., in gastroenterology [10][11][12][13], endocrinology [14], and rheumatology [15,16].…”
Section: Introductionmentioning
confidence: 90%